Cannabis, risk and normalisation: Evidence from a Canadian study of socially integrated, adult cannabis users - Duff, Cameron; Erickson, P. (2014)
Howard Parker's 'normalisation thesis' has made a significant contribution to youth drug studies in many countries. Parker's thesis has been less investigated, however, for its application across the life course, and few scholars have considered its utility for assessments of the meaning and experience of drug-related health risks. This article adds to discussions of drugs, normalisation and risk by analysing qualitative data collected from 165 long-term cannabis users aged 20-49 years in four Canadian provinces between 2008 and 2010. We focus on participants' assessments of the risks and harms associated with persistent cannabis use and the strategies they employed to mitigate these risks. Our findings indicate important distinctions between culturally mediated conceptions of cannabis-related risks and the more narrowly grounded perception of cannabis harms based on personal or peer experience. These distinctions correspond with participants' reports of a significant shift in cannabis' risk profile in Canada. Participants attributed this shift to three factors: the growing prevalence of cannabis use; the rise of 'medical marijuana' and renewed attention to the drug's therapeutic benefits and what they perceived to be the low incidence of cannabis-related harms in Canada. We conclude that understanding how health risks are assessed and managed by cannabis users should help to clarify how and why more tolerant attitudes about cannabis have emerged in Canada and how this change may impact on non-users' expectations about any future initiation of use. We close by reflecting on the implications of our findings for cannabis-related public health, education and harm reduction initiatives. © 2014 © 2014 Taylor & Francis.